(untitled) (Psicologia USP, 2001)
The work with groups, a valuable tool in institutional spaces, is becoming more and more vulgarized because of a tendency toward a mere technical approach. This article is intended to be a contribution to group coordination. It keeps away from the study of the coordinators personality, suggesting that they be understood as mediators between experiencing and critical understanding. Thus pointing out their constructive role in group processes.